Expressão de proteínas envolvidas na apoptose e sua relação com o índice proliferativo em melanomas caninos - Bárbara Andrade de Carvalho (2019)
Melanoma is an extremely aggressive neoplasm, although it’s morbidity is not so significant among skin cancers. It has a high mortality rate in both human and veterinary medicine. In addition, canine melanoma, due to its histopathological and molecular characteristics similar to the human ones, is considered a good model for comparative studies of development and neoplastic progression. It is known that na important parameter of tumor aggressiveness is the proliferative and apoptotic index, where more aggressive tumors must present higher rates of cell proliferation and lower rates of apoptosis. In this context, resistance to apoptosis is described as na important feature related to tumor development. The study of apoptosis, na event still poorly understood in melanomas, may help in understanding the aggressiveness and progression of these tumors. Thus, this work aims to characterize and correlate the immunohistochemical expression of Ki67, Bcl-2, Bax, Caspase-3, Caspase-3 cleaved and Caspase-9 cleaved, as well as the histopathological features observed in canine melanomas. We selected 40 cases of cutaneous and oral canine melanomas for histopathological evaluation (presence of plunger, desmoplasia, junctional activity, mitotic index, ulceration) and immunohistochemical technique. Among the biomarkers, Ki67 correlated only with Bax expression, positively, Bcl-2 was positively related to cleaved Caspase-3 and Caspase-9 cleaved, and the elevation of cleaved Caspase-3 expression is related to increased expressionof Caspase-9 cleaved. Was observed a significant difference when the low and high Ki67 expression groups and the low and high expression groups of Caspase-3 cleaved (35% of cases with low expression of both biomarkers) were associated. Among the oral and cutaneous groups, the second presented a greater expression of Caspase-9 cleaved. No association was found between the mitotic index, the histological characteristics and the high and low expression groups of the immunohistochemical biomarkers studied. Thus, our work has shown that increased cell proliferation and increased expression of anti-apoptotic proteins are related to an increase in the expression of pro-apoptotic proteins. It was also observed that oral melanomas, considered to be more aggressive, have lower expression of apoptosis cascade inducing protein when compared to cutaneous melanomas.